2018
DOI: 10.1007/s00493-017-3605-0
|View full text |Cite
|
Sign up to set email alerts
|

Diameter of Ramanujan Graphs and Random Cayley Graphs

Abstract: We study the diameter of LPS Ramanujan graphs Xp,q. We show that the diameter of the bipartite Ramanujan graphs is greater than (4/3) log p (n) + O(1) where n is the number of vertices of Xp,q. We also construct an infinite family of (p + 1)-regular LPS Ramanujan graphs Xp,m such that the diameter of these graphs is greater than or equal to (4/3) log p (n) . On the other hand, for any k-regular Ramanujan graph we show that the distance of only a tiny fraction of all pairs of vertices is greater than (1 + ) log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…This generalizes the celebrated result of Bourgain and Gamburd on the expansion of random Cayley graphs on SL 2 [Z/pZ][BG08]. As a consequence of the work of Lubetzky and Peres[LP15] or the second author[Tal15a], our conjecture implies that a random symmetric set of generators with 2d elements represents almost all elements of SL…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This generalizes the celebrated result of Bourgain and Gamburd on the expansion of random Cayley graphs on SL 2 [Z/pZ][BG08]. As a consequence of the work of Lubetzky and Peres[LP15] or the second author[Tal15a], our conjecture implies that a random symmetric set of generators with 2d elements represents almost all elements of SL…”
supporting
confidence: 81%
“…On the other hand, the diameter of the Cayley graph with LPS generators that is a special fixed generator family of Cayley graphs is not optimal. The second named author in [Tal15a], showed that the diameter of a family of LPS Ramanujan graphs is greater than 4/3 log d−1 (n) where n is the number of vertices and d is the degree of the graph. This lower bound is related to the repulsion of integral points lying on quadrics.…”
mentioning
confidence: 99%
“…Sardari in an insightful paper [31] posted to the arXiv a few months after the initial posting of the present paper. For a certain infinite family of (p + 1)-regular n-vertex Ramanujan graphs, Sardari [31] shows that the diameter is at least 4 3 log p (n) and also gives an alternative proof of the first part of Corollary 2.…”
Section: 1mentioning
confidence: 99%
“…Then Theorem 1.6 gives us the following: Theorem 1.6 (Theorem 1.3 in [14]). First, let k be an integer at least 3, and let G be a k -regular nonbipartite Ramanujan graph.…”
Section: Our Results and Techniquesmentioning
confidence: 99%
“…Another critical property of Ramanujan graphs that we will use is Theorem 1.6 below, which was very recently established by N. Sardari [14], and says that the average distance between pairs of vertices in a Ramanujan graph is small. More precisely: Definition 1.5.…”
Section: Our Results and Techniquesmentioning
confidence: 99%